Children as agents of cultural adaptation - Lew-Levy, Sheina; Amir, Dorsa (Behavioral and Brain Sciences)
The human capacity for culture is a key determinant of our success as a species. While much work has examined adults' abilities to create and transmit cultural knowledge, relatively less work has focused on the role of children (approx. 3-17 years) in this important process. In the cases where children are acknowledged, they are largely portrayed as of cultural knowledge from adults, rather than cultural producers in their own right. In this paper, we bring attention to the important role that children play in cultural adaptation by highlighting the structure, function, and ubiquity of the large body of knowledge produced and transmitted by children, known as . Supported by evidence from diverse disciplines, we argue that children are independent producers and maintainers of these autonomous cultures, which exist with regularity across diverse societies, and persist despite compounding threats. Critically, we argue peer cultures are a source of community knowledge diversity, encompassing both material and immaterial knowledge related to geography, ecology, subsistence, norms, and language. Through a number of case studies, we further argue that peer culture products and associated practices - including exploration, learning, and the retention of abandoned adult cultural traits - may help populations adapt to changing ecological and social conditions, contribute to community resilience, and even produce new cultural communities. We end by highlighting the pressing need for research to more carefully investigate children's roles as active agents in cultural adaptation.
Accepted manuscript available online 26th December 2024
Keywords: peer culture; cultural evolution; child culture; cultural adaptation; cultural diversity; human life history